2016
DOI: 10.1186/s12885-016-2160-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a computer-aided diagnosis system involving bone scans among men treated with docetaxel for metastatic castration-resistant prostate cancer

Abstract: BackgroundThe bone scan index (BSI), which is obtained using a computer-aided bone scan evaluation system, is anticipated to become an objective and quantitative clinical tool for evaluating bone metastases in prostate cancer. Here, we assessed the usefulness of the BSI as a prognostic factor in patients with metastatic castration-resistant prostate cancer (mCRPC) treated using docetaxel.MethodsWe analyzed 41 patients who received docetaxel for mCRPC. The Bonenavi system was used as the calculation program for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…However, they sometimes experience that patients' symptoms worsen, and the results of imaging are poor even if an absolute value of the PSA is low. Furthermore, the PSA value might not become the prognostic marker . As advanced prostate cancer often metastasizes to bone, it is extremely important to evaluate the change of bone metastasis.…”
Section: Evaluation Of Imagementioning
confidence: 99%
See 1 more Smart Citation
“…However, they sometimes experience that patients' symptoms worsen, and the results of imaging are poor even if an absolute value of the PSA is low. Furthermore, the PSA value might not become the prognostic marker . As advanced prostate cancer often metastasizes to bone, it is extremely important to evaluate the change of bone metastasis.…”
Section: Evaluation Of Imagementioning
confidence: 99%
“…Furthermore, the PSA value might not become the prognostic marker. 62,63 As advanced prostate cancer often metastasizes to bone, it is extremely important to evaluate the change of bone metastasis. The extent of disease on bone scintigraphy was used to stratify the level of bone metastasis.…”
Section: Evaluation Of Imagementioning
confidence: 99%
“…reported that a BSI ≥1% predicted survival in metastatic castration‐resistant prostate cancer patients, whereas Miyoshi et al . reported a BSI ≥1.9% predicted survival in metastatic castration‐sensitive prostate cancer patients . Anand et al .…”
mentioning
confidence: 99%
“…The BSI has been adopted in the assessment of bone metastasis among hormone‐naïve to hormone‐resistant prostate cancer . The cut‐off of the BSI in predicting worse survival varies from 1% to 5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation